Arginine supplementation improves growth, antioxidant capacity, immunity and disease resistance of juvenile Chinese mitten crab, Eriocheir sinensis. Issue 93 (October 2019) - Qi, Changle; Wang, Xiaodan; Han, Fenglu; Jia, Yongyi; Lin, Zhideng; Wang, Chunling; Lu, Jianting; Yang, Lu; Wang, Xinyue; Li, Erchao; Qin, Jian G.; Chen, Liqiao
Abstract: To investigate the effects of arginine (Arg) on the growth, antioxidant capacity, immunity and disease resistance of juvenile Chinese mitten crab, three diets containing Arg levels at 1.72% (control), 2.73% and 3.72% were formulated and fed to Chinese mitten crab (0.22 ± 0.03 g) for eight weeks. The weight gain, ecdysterone and growth hormone in the serum, relative expression of insulin-like growth factor 2 in the hepatopancreas significantly increased in crabs fed the 2.73% and 3.72% Arg diets. The protein and lipid contents significantly increased in crabs fed the 3.72% Arg diet. The feed conversion ratios in crabs fed the diets with Arg additions were lower than in the control. Arg supplementation also enhanced the antioxidative capacity by increasing the activities of superoxide dismutase, catalase and the relative expression of Kelch-like ECH-associated protein 1 gene in the hepatopancreas, which subsequently decreased malondialdehyde content in the hepatopancreas. Besides, Arg also decreased nitric oxide content in the serum and the activity of nitric oxide synthetase in the hepatopancreas. The relative mRNA levels of crustin, relish, lysozyme and cryptocyanin genes were significantly upregulated by Arg supplementation. The activities of acid phosphatase and alkaline phosphatase in the serum significantly increased in crabs fed the 3.72% Arg diet than those in the control. Similarly, the relative mRNA levels of crustin, cryptocyanin and proPO genes were significantly upregulated in crabs fed the 2.73% Arg diet after lipopolysaccharide challenge, and in crabs fed the 3.72% Arg diet after the Poly (I:C) challenge. The crabs fed the 2.73% and 3.72% Arg diets had higher survival rate after bacterial infection than those fed the control diet. This study indicates that the addition of Arg to the diet at 2.7–3.7% can improve the growth, survival, antioxidant capacity, immunity and disease resistance in juvenile Chinese mitten crab. Highlights: Arginine promoted the weight gain and survival rate of Chinese mitten crab. Arginine improved the antioxidant capacity and immunity of Chinese mitten crab. Arginine enhanced the disease resistance of Chinese mitten crab. Arginine is one of the critical amino acids in Chinese mitten crab aquaculture.